The use of the Moodle platform by visually impaired students: an interaction analysis based on usability assumptions - Bernardino de Oliveira, Silvio; de Souza Galdino Acioly, Angélica (InfoDesign, 2024)
The use of Virtual Learning Environments (VLE) became quite common during and after the COVID-19 Pandemic. Thus generating a major challenge – promoting better interaction between different platforms with their users and their specificities. This article, therefore, presents the results of a survey that analyzed the interaction of students with visual impairments with Moodle Platform, focusing on usability. The research took a mixed and exploratory approach, based on a case of study, following the procedures of Lima (2012) and the assumptions of ISO ABNT NBR 9241-171. As results, the research, in general terms, indicated some usability problems which hinder the autonomy and involvement of this audience, such as: interfaces overloaded with text, excessive dependence on visual resources to transmit information, insufficient feedback in interactions, among others. The article also presents some recommendations for better adapting the platform’s interface design to the target audience.